2014
DOI: 10.1117/1.jbo.19.1.015007
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced tissue fluorescence in radiofrequency tissue-fusion characterization

Abstract: Abstract. Heat-induced tissue fusion is an important procedure in modern surgery and can greatly reduce trauma, complications, and mortality during minimally invasive surgical blood vessel anastomosis, but it may also have further benefits if applied to other tissue types such as small and large intestine anastomoses. We present a tissue-fusion characterization technology using laser-induced fluorescence spectroscopy, which provides further insight into tissue constituent variations at the molecular level. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Various techniques have been employed recently to study collagen ex vivo and in vivo which includes simple, quick and economical biochemical estimation and LIAF spectroscopy ; much complex and costly immunohistochemical staining , atomic force microscopy , second harmonic generation imaging , high‐performance liquid chromatography combined with mass spectrometry , fluorescence imaging and fluorescence lifetime imaging , optical coherence tomography , small angle X‐ray and magnetic resonance imaging . Laser‐induced spectroscopy is an attractive noninvasive label‐free method for extracting information from endogenous fluorophores for tissue characterization . Additionally, this technique provides vital medical information from innately present intrinsic fluorophores in the real‐time necessary for disease diagnosis and treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques have been employed recently to study collagen ex vivo and in vivo which includes simple, quick and economical biochemical estimation and LIAF spectroscopy ; much complex and costly immunohistochemical staining , atomic force microscopy , second harmonic generation imaging , high‐performance liquid chromatography combined with mass spectrometry , fluorescence imaging and fluorescence lifetime imaging , optical coherence tomography , small angle X‐ray and magnetic resonance imaging . Laser‐induced spectroscopy is an attractive noninvasive label‐free method for extracting information from endogenous fluorophores for tissue characterization . Additionally, this technique provides vital medical information from innately present intrinsic fluorophores in the real‐time necessary for disease diagnosis and treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies offered a preliminary report on the biochemical mechanisms of vascular fusion, a definitive correlation of fusion adhesion to collagen cross-linking or renaturation was not established. Nevertheless, the assumption that thermal tissue welding was a by-product of collagen renaturation and/or potential cross-linking prevailed in the subsequent literature (4,14,38,53,65,(68)(69)(70)(71). In 1997, Tang et al (14) observed the morphological "roping" of parallel collagen fibers after welding, which was proposed to complement the end-to-end interdigitation observed by Schober et al (17).…”
Section: Qualitative Observations Of Denaturation And/or Collagen Cross-linking Early Imaging Work Bymentioning
confidence: 98%
“…However, there is evidence that recoverable fusion has advantages similar to those of vessel sealing relative to sutures in decreased perioperative blood loss (34) and minimized scarring in dermal tissue (4,5). Similarly, experimental fusion has been explored with promising results for a watertight union with functional recovery of such vascular, fluid-carrying tissues as the small and large bowel (35)(36)(37)(38), where the success of this procedure was measured in the ability of the tissue to heal across the fused boundary and function as originally intended, inclusive of peristalsis. Energy-based fusion has also been suggested and investigated for the thermal union of transected or pathological neurons without tissue deficit (28), indicating that neurological impulses were communicated across a healed, and thus functionally recovered, fusion boundary.…”
Section: Prospective Applicationsmentioning
confidence: 99%
“…SG B included animals that, after applying the components of tissue growth factors (0.5-1 ml) to the zone of sutures and then covering the suture line with a synthetic coating, conducted electromagnetic irradiation of the zone of intestinal sutures with a wavelength of λ 660 nm (which corresponds to red light). The wavelength of the electromagnetic irradiation and the nature of the coating were chosen by us on the basis of literature data and the results of our own preliminary experimental studies [11,12,13,14]. The surviving animals were removed from the experiment on the 5th day of the experiment by decapitation.…”
Section: експериментальні дослідженняmentioning
confidence: 99%